Reality is interface: Two motion capture case studies of human–machine collaboration in high-skill domains. (December 2016) - Bard, Joshua David; Blackwood, David; Sekhar, Nidhi; Smith, Brian
This article explores hybrid digital/physical workflows in the building trades, a high-skill domain where human dexterity and craft can be augmented by the precision and repeatability of digital design and fabrication tools. In particular, the article highlights two projects where historic construction techniques were extended through live motion capture of human gesture, information-rich visualization projected in the space of fabrication and custom robotic tooling to generate free-form running moulds. The first case study explores decorative plastering techniques and an augmented workflow where designers and craftspeople can quickly explore patterns through freehand sketch, test ideas with shaded previews and seamlessly produce physical parts using robotic collaborators. The second case study reimagines a roman vaulting technique that used terracotta bottles as part of an interlocking masonry system. Motion capture is used to place building elements precisely in material arrays with real-time visual feedback guiding the hand-held placement of each bottle. These case studies serve to underscore the emerging importance of reality capture in the design and construction of the built environment. Increasingly, the algorithmic power of computational tools and the nuances of human skill can be combined in hybrid design and fabrication workflows.